This "mite" Surprise You: Scabies Masquerading as Langerhans Cell Histiocytosis - A Case Report - Sara Al Janahi; Raghda Al Maashari; Tausif Saleem (Karger Publishers, 2024)
Introduction: Scabies is a common parasitic infestation caused by the mite Sarcoptes scabiei. Scabies can mimic other entities clinically, resulting in misdiagnosis. The presence of a mite in the stratum corneum on biopsy specimens is diagnostic of scabies. However, there are instances when mites are not visible, and immunohistochemical (IHC) staining may be misleading. An example is when IHC demonstrates Cluster of Differentiation 1a and S100 positivity. The main differential diagnosis for this finding is Langerhans cell histiocytosis, a group of idiopathic disorders of bone marrow-derived Langerhans cells, with manifestations ranging from isolated to life-threatening multisystem disease. Case Presentation: We present a case of a patient who was diagnosed with Langerhans cell histiocytosis based on histological findings, further review with a repeat reading and deeper sectioning of her biopsy revealed a mite in the stratum corneum, altering the diagnosis, course, and management. She subsequently developed persistent post-scabietic nodules, an underreported entity that may occur following infestation and persist for up to a year. These lesions are self-limiting and do not require repeated courses of treatment. Conclusion: Langerhans cell hyperplasia may be seen in a multitude of entities, including scabies. Familiarity with this phenomenon is crucial to avoid unnecessary invasive investigations, aggressive management and alleviate patients' concerns.